THE HARMONY OF MEDICINE, LAW AND FIQH IN PROTECTING HUMAN LIFE AND DIGNITY (The Journal of Interdisciplinary Human Studies, 2026)
This article analyzes the interrelation and shared objectives of medicine,law, and fiqh (Islamic jurisprudence) in protecting human life and dignity. It examinesthe role of medicine in preserving human health, the function of the legal system inguaranteeing human rights, and the principles of Islamic law concerning the protection ofhuman life and honor. On the basis of medical deontology, bioethics, national legislation,and juridical (fiqh) maxims, the article reveals the scientific and practical significanceof these three domains.
Keywords: medicine, law, fiqh, bioethics, deontology, human life, human dignity, maqasid al-shari’a, medical law, ethics.